Antagonism potency of dark Septate endophytes against Pyricularia oryzae for improving health of rice plants - Dini Yuliani; Bonny P. W. Soekarno; Abdul Munif; Surono Surono (Jurusan Agroteknologi, 2020)
Blast disease caused by Pyricularia oryzae (Po) is the main disease affecting rice production. Dark septate endophytes (DSEs) is known to improve plant performance and suppress disease. This study evaluated DSEs antagonism potency against P. oryzae in improving the rice plant's health. The research stages consisted of: (1). DSE and Po growth rate; (2). Antagonism of DSEs against Po; (3). Chitinase; (4). DSEs Viability; (5). DSEs application to rice seeds in nurseries. The results showed the growth of APDS 3.2 colonies had fulfilled Petri (d = 9 cm) at three days after incubation (DAI), while 4.1 BTG and TKC 2.2.a at 7 DAI. Po had slow colony growth required 20 DAI. Inhibition of APDS 3.2 against Po was 43.75%, higher than of 4.1 BTG (38.60%) and of TKC 2.2.a (39.76%). The rice plants inoculated with APDS 3.2 had a relatively higher at seedling height, root length, wet weight, and dry weight than those inoculated with TKC 2.2.a and 4.1 BTG. The highest DSEs colonization was found in APDS 3.2 at 50.56%, followed by TKC 2.2.a (46.67%) and 4.1 BTG (40%). DSEs fungus has the potential to suppress rice blast pathogens by improving the health of rice plants, especially APDS 3.2.Key words: Colonization, Growth Rate, Viability Penyakit blas yang disebabkan oleh Pyricularia oryzae (Po) merupakan penyakit utama yang memengaruhi produksi padi. Dark septate endophyte (DSE) diketahui mampu meningkatkan performa tanaman dan menekan penyakit. Penelitian ini bertujuan untuk mengevaluasi potensi antagonisme DSE terhadap P. oryzae dalam meningkatkan kesehatan tanaman padi. Tahapan Penelitian terdiri atas: (1). Kecepatan tumbuh DSE dan Po; (2). Antagonisme DSE terhadap Po; (3). Kitinase; (4). Viabilitas DSE; (5). Aplikasi DSE pada benih padi di persemaian. Hasil penelitian menunjukkan pertumbuhan koloni APDS 3.2 telah memenuhi petri (d= 9 cm) pada 3 hari setelah inkubasi (HSI), sedangkan 4.1 BTG dan TKC 2.2.a pada 7 HSI. Pertumbuhan koloni Po lambat membutuhkan 20 HSI. Penghambatan APDS 3.2 terhadap Po sebesar 43,75% lebih tinggi dibandingkan 4.1 BTG (38,60%) maupun TKC 2.2.a (39,76%). Tanaman padi yang diinokulasi APDS 3.2 memiliki tinggi, panjang akar, bobot basah, dan bobot kering relatif lebih tinggi dibandingkan yang diinokulasi TKC 2.2.a dan 4.1 BTG. Kolonisasi DSE tertinggi dijumpai pada APDS 3.2 sebesar 50,56%, diikuti TKC 2.2.a (46,67%) dan 4.1 BTG (40%). Cendawan DSE memiliki potensi untuk menekan patogen blas padi dengan cara meningkatkan kesehatan tanaman padi, khususnya APDS 3.2.